Bromley's family law - Lowe, N. V.
This latest edition reflects the general trends in the development of family law, in particular the increasing emphasis upon the parent-child relationship and the diminishing significance of marriage. Therefore substantial changes have been made both to the overall structure and to the content. For example, the chapters on Divorce and Family Protection have been entirely re-written in the light of the Family Law Act 1996